THE DISTRIBUTIONS OF COLLOIDAL AND DISSOLVED ORGANIC CARBON, MAJOR ELEMENTS, AND TRACE ELEMENTS IN SMALL TROPICAL CATCHMENTS - Eyrolle F.; Benedetti M.F.; Benaim J.Y.; Fevrier D. (My University, 1996)
In tropical surface waters, ultrafiltration, differential pulse anodic stripping voltametry, and atomic absorption spectrometry were used to determine the distribution and association of major and trace elements with different size fractions of dissolved organic carbon (DOC < 0.45 μm). DOC is mainly concentrated in the low molecular size ranges (<20 kD). However, in podzolization areas, an important part of the DOC is found in the higher molecular weight fractions (20 kD < DOC < 100 kD). The higher molecular weight fractions have a higher site density. Complexation capacities are in the range of 1-11 μM in bulk solution. In podzolization areas the higher molecular weight fractions control the speciation of Ca, Mg, and Fe. In the other tropical environments major elements are present as free ions and the low molecular weight fraction of DOC controls the speciation of trace metals (Cu).